Cybersecurity guide: 3 Books in 1 - From Beginner to Pro: The Complete Guide to Developing and Implementing Effective Cybersecurity Strategies in Three Levels - Logan, Ethan Cybersecurity expert (United States : North Haven, CT, 2023)
This comprehensive guide offers three books in one, providing readers with a complete journey from beginner to pro in the field of cybersecurity. The first book is tailored to beginners, offering an introduction to cybersecurity and outlining strategies for developing and implementing effective security measures. The middle-level guide delves deeper into the subject matter, offering a more detailed analysis of cybersecurity threats and providing readers with practical tools and techniques to enhance their security posture. Finally, the pro-level guide provides advanced insights into cybersecurity strategies, offering detailed advice on how to develop and implement effective security protocols at the highest levels. Whether you're a novice or a seasoned pro, this guide has something to offer, providing readers with the knowledge and tools needed to stay ahead of the ever-evolving landscape of cybersecurity threats.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Coding Security -- Computer networks -- Security measures; Computer security; Computer crimes -- Prevention